Effect of Contamination with Hemostatic Agent on Shear Bond Strength of Composite to Dentin Using G-Premio and Single Bond Universal Adhesives - Zahra Khamverdi; Naemeh Karimian; Maryam Farhadian; Hamed Gheitouli (Tehran University of Medical Sciences, 2021)
Objectives: Bond strength of composite restorations plays an important role in their success. This in vitro study evaluated the effect of a hemostatic agent on shear bond strength of universal adhesives. Materials and Methods: Thirty-six extracted human molars were used in this study. Buccal and lingual surfaces were reduced to obtain flat dentin surfaces and were ground with a silicone paper. The samples were randomly divided into three groups (n=12) based on the application of hemostatic agent: group 1: no contamination (control), group 2: aluminum chloride application, and group 3: ferric sulfate application. Each group was then divided into two subgroups (n=6) for using G-Premio and Single Bond Universal. Resin cylinders (Filtek Z550) were bonded to dentin surfaces according to the manufacturer's instructions. After 1000 thermal cycles, shear load was applied to the specimens using a universal testing machine at a crosshead speed of 1 mm/min until failure. Data were statistically analyzed using two-way ANOVA and Tukey's post-hoc test (α=0.05). Results: There were statistically significant differences in shear bond strength of the three main groups for both G-Premio and Single Bond Universal (P<0.05). When the adhesive systems were compared with each other, G-Premio showed higher shear bond strength than Single Bond Universal (P<0.05). Conclusion: Contamination with hemostatic agents had an adverse effect on the shear bond strength of universal adhesives. Moreover, G-Premio yielded a higher bond strength than Single Bond Universal. Keywords: Hemostatics; Shear Strength; Adhesives